Incidence of Epinephrine Reactions With Local Anesthesia in Mohs Micrographic Surgery. Issue 5 (May 2020) - McLawhorn, Justin M.; Clark, Summer; Lander, Steven; Truong, Valerie; Aston, Christopher E.; Collins, Lindsey; Stasko, Thomas
Abstract : BACKGROUND: The incidence of reactions to epinephrine-containing local anesthetics in Mohs micrographic surgery (MMS) has not been established. OBJECTIVE: To estimate the incidence of epinephrine-induced reactions from local anesthetics in patients who undergo MMS for the removal of cutaneous malignancies. METHODS: From 2016 to 2018, 200 MMS patients were recruited from the authors' surgical center. Assessments were obtained throughout the entirety of the Mohs cases during a single visit. RESULTS: This study estimated the incidence of epinephrine reactions in patients who undergo MMS to be 2.0% (95% confidence interval: 0.1%–3.9%). No relationship between epinephrine dose and incidence of adverse effects was found. Patient age was a significant risk factor for the development of an epinephrine reaction. CONCLUSION: Systemic reactions to epinephrine from local anesthetics are an infrequent adverse event in MMS cases. The data suggest that the absolute dose of local anesthetic with epinephrine does not correlate with the risk of developing an epinephrine reaction. Older age seems to have a protective effect.